The Study of Marketing Mix within Higher Schools - PUGACH, Valentin Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The development of civilization in the period of shift from the industrial to the information society leads to a logical reform of the education system, which is one of the key factors in the development of any country. The marketing activities in the education sector have a fairly wide range of applications. Therefore, the marketing mix is a necessary tool for managing higher schools. The modern Russian educational institutions should become powerful research and educational centres, capable to adapt to the current market conditions applying their marketing functions, taking into account the global development patterns of the education sector and to ensure its development in the context of globalization. Becoming a successful higher school, like any enterprise, operating in the market environment, is possible due to the conformity of consumer attributes to consumer preferences. This aspect takes into consideration the marketing mix.
Keywords: knowledge economy; marketing; marketing mix; education sector; market; marketing activities